Funds-Flow Equations. - Johnson, Glenn L. (The Accounting Review, 1966)
The article focuses on funds flow. Recent accounting literature has produced two articles on mathematizing funds flow. One of the approaches undertaken shows algebraically that the net change in working capital is explained by the changes in non current assets and equities. This article attempts to analyze algebraically the individual changes in non current accounts and thereby provide a means to calculate directly through equations the individual sources and uses of working capital needed for a funds statement. In addition, an algebraic system for cash-flow analysis is also discussed. The algebraic approach provides a flexible means to adapt to different concepts of funds, such as net working capital, cash flow, and net quick assets. The algebraic expression of funds flow is consistent with the trend towards computerized accounting. The equations can be programmed readily and used to generate funds statements. This article uses a complete set of equations to tie together the funds flow from the income statement and balance sheet items, to show the elimination of non fund items, and to show the individual sources and uses of funds in the non current accounts.